Impact of Momordica Charantia (Karela) on the Fasting Blood Glucose level in the Streptozotocin-Induced Diabetic Rats - Mohal, S; Mondal, DK; Chowdhury, PK; Khanom, A; Shamim, KM (Bangladesh Journal of Anatomy, 2011)
Context: Scientific studies revealed the hypoglycaemic properties of momordica charantia. The present study was carried out to find out microscopically whether Momordica charantia (karela) has got any impact lowering of FBG (Fasting Blood Glucose) level in diabetes mellitus. Study type: an experiemental study. Setting: Anatomy department of the then IPGMR (Institute of Post Graduate Medicine and Research) at present BSMMU (Bangabandhu Sheikh Mujib Medical University) and BIRDEM (Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine & Metabolic Disorders). Subjects: Sixty five healthy young Long Evans rats of male sex weighing 150 to 280gm aged between 10 to 12 weeks were used in this study. Methods: The rats were divided into four equal groups depending on their different sorts of dietry feeding and drug treatment. Main outcome measures: variation of differential FBG level in different groups of rat. Result: Mean 'initial' and 'final' (on day 7 and day 51 from Streptozotocin/vehicle injection) fasting blood glucose (FBG) level in the control group (Group-A) was 7.872 ± 0.60 and 8.55 ± 0.82 respectively. Therefore the mean (FBG) increased by about 13% (P = 0.022*) which is higher than that of the initial value. In untreated diabetic group the mean initial (FBG) level was 25.95 ± 8.90 and the mean final was 24.02 ± 4.08. So here, the (FBG) level decreased by about 13% (P = 0.557). On the other hand, in the insulintreated diabetic rats the mean initial (FBG) level was 24.35 ± 6.81 and the mean final was 8.38 ± 5.02, which is lower (P = 0.000*) & in the karela–treated diabetic rats, the initial (FBG) level was 23.03 ± 5.70 and the mean final was 5.65 ± 1.29 which is lower* (P = 0.000*). The value in the insulin-treated diabetic rats & in the karela-treated diabetic rats were significantly lower than that of the untreated diabetic rats (P = 0.007) & (P= 0.005) respectively. But there was no significant difference between the insulin-treated diabetic rats & the karela-treated diabetic rats (P = 0.605) in this regard. Conclusion: Karela showed a tendency of acting against hyperglycemic effects of Streptozotocin-induced diabetes mellitus. However, further investigations are recommended for establishing karela as a safe, useful effective anti- hyperglycemic agent as well as antidiabetogenic agent. Key words: Diabetes mellitus; Hyperglycemia; Momordica charantia (karela) DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8148 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 45-48